Almost Partitioning 2-Edge-Colourings of 3-Uniform Hypergraphs with Two Monochromatic Tight Cycles - Han, H (Elsevier B.V., 2017)
We show that any 2-colouring of the 3-uniform complete hypergraph Kn(3) on n vertices contains two disjoint monochromatic tight cycles of distinct colours covering all but o(n) vertices of Kn(3). The same result holds if we replace tight cycles with loose cycles. © 2017 Elsevier B.V.